(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
The breakdown of the Soviet Unionsurprised most scholars of international relations, comparative politics, andSoviet politics. Existing explanations attribute the breakdown of the Soviet Union to the reformist leadership of Gorbachev,and/or to systemic factors. These explanations do not focus on the keycontribution of the war in Afghanistan. This is surprising since many scholars view wars as keycausal factors in empire breakdown and regime change. We argue that the war in Afghanistan was a key factor, though not theonly cause, in the breakdown of the Soviet Union.The war impacted Soviet politics in four reinforcing ways: (1) Perceptioneffects: it changed the perceptions of leaders about the efficacy of using themilitary to hold the empire together and to intervene in foreign countries; (2)Military effects: it discredited the Red Army, created cleavage between theparty and the military, and demonstrated that the Red Army was not invincible,which emboldened the non-Russian republics to push for independence; (3)Legitimacy effects: it provided non-Russians with a common cause to demandindependence since they viewed this war as a Russian war fought by non-Russiansagainst Afghans; and (4) Participation effects: it created new forms ofpolitical participation, started to transform the press/media before glasnost,initiated the first shots of glasnost, and created a significant mass of warveterans (Afghansti) who formed new civil organizations weakening the politicalhegemony of the communist party. The Soviet-Afghan War was a remarkable event in history.Like their ancestors, the Afghans battled a hostile, invading force thatattempted to dominate their homeland. But for the first time, Afghanistanwould become the center of a modern pan-Arab Jihad (Holy War). Like theirancestors who fought in the Anglo-Afghan Wars, the modern Afghans fought a warof attrition. But the use of modern weaponry would beget casualties andemigration of greater proportions. Like their ancestors, the modern Afghanstriumphed over their oppressors. But for the first time, they would triumphwith the help of a large and complex global coalition of superpowers, middlepowers, and regional powers. This conflict triggered a chain of events which wouldplunge Afghanistaninto almost three decades of brutal warfare. By the end of the war, theU.S.S.R. was on the verge of collapse; the Afghans and their allies appeared tohave won a major victory. So what caused this unexpected upset? It appearsthat the Soviet Union lost the Soviet-Afghan War due to its own mistakes, thecommitted involvement of an international “Coalition” which supported theMujahedeen, and the contributions made by the Mujahedeen and the Afghanipeople.